Strategic Management of An International Company in The Digital Economy - Wenbin Fan; Jielin Zhao (Communications of International Proceedings, 2022)
The modern world will never be the same again. And all this thanks to information technology and digitalization, which have changed and facilitated business processes, and also opened up completely new opportunities for companies around the world. Market conditions have raised the question of the forms and methods in a new way, with the help of which it is possible to assess the result of the activities of knowledge-intensive enterprises and the degree of their functioning. In a competitive environment, it is important for companies not only to avoid shortages, but also to develop successfully. This can be obtained thanks to deep knowledge in the field of production organization or modern digital technologies. In this regard, at present, industrial enterprises use information and communication technologies and information systems that provide a solution to the problems of managing the stages of the product life cycle for the implementation of a single information space. Thus, the importance of digitalization is increasing, since the implementation of these tasks requires an orderly information base for effective management decision-making.
Keywords: Digital economy; strategic management; digitalization; information technology; automotive.